Problematika Waria Dalam Eksistensinya Di Masyarakat Beragama Studi Pendekatan Waria di Pondok Pesantren Al-Fatah Yogyakarta - Mahatva Yoga Adi Pradana; Ika Atania Rahmah; Tsani Tsani Alwin (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2021)
A man or so-called transvestite is a man who looks like a woman. In Islam, transvestites are called Mukhanast which means to be a woman. The issue of transvestites has not been resolved well in society until now. Its existence is often opposed so that it is marginalized. Various efforts made by transvestites so that their existence is accepted by the community, one example is the establishment of Al-Fatah Boarding School which is evidence of transvestite expression that is considered worthy of fulfilling its religious rights. Transvestites want their existence to be seen as human beings in general, getting the same rights, especially in the protection of law and the construction of the role of society.